Exploring the Value Proposition of Primary Care for Safety-Net Patients Who Utilize Emergency Departments to Address Unmet Needs - Kimberly R. Enard; Deborah M. Ganelin (SAGE Publishing, 2017)
Background: An underlying assumption of strategies intended to promote appropriate primary care over emergency department (ED) use for ongoing health care needs is that patients will understand the "value proposition" of primary care: that they will receive specific benefits from primary care providers over and above what they receive from EDs. However, there is evidence that this value proposition may be unclear to safety-net patients. The goals of this study are to describe factors motivating ED use for low-acuity conditions; describe similarities and differences in usual source of care (USOC) experiences, by ED versus non-ED setting; and assess awareness and perceptions of the patient-centered medical home (PCMH) concept among safety-net patients. Methods: We conducted a cross-sectional descriptive study of adult patients (n = 329) at 3 safety-net hospitals in the Southwest. Results: Key reasons for ED use were perceived urgency, lack of awareness about other options for care, payment flexibility, and perceived quality and convenience. Approximately half of participants indicated they would seek treatment in non-ED settings, if available, but agreement differed by group (non-ED USOC, 60.2%; ED USOC, 50.7%; no USOC, 45.3%; P = .025). Agreement that providers coordinated access to needed medical services was significantly higher among patients with non-ED USOCs; agreement that providers coordinated non-medical services that facilitate access to care was similar (approximately 45%) for patients with ED and non-ED USOCs. Approximately 70% of participants in both groups agreed that every person should have a medical home. Conclusions: Perceived experiences of care in ED and non-ED USOC settings suggest challenges and opportunities for increasing the value proposition of primary care for safety-net patients. Although patients are receptive to the PCMH concept, effective strategies to better highlight the value of primary care in coordinating both medical and related nonmedical services and other PCMH benefits warrant further investigation.